PEMANFAATAN MINYAK ATSIRI KAYU MANIS MENGENDALIKAN CENDAWAN Neocytalidium dimidiatum PENYEBAB STEM CANKER PADA BUAH NAGA (Hylocereus sp.) SECARA IN-VITRO - Extri Okina; Sulhaswardi; Rizka (DINAMIKA PERTANIAN, 2023)
This study aims to determine the effectiveness of several concentrations of cinnamon essential oil to control stem canker disease in dragon fruit caused by the fungus Neocytalidium dimidiatum. This research was conducted at the Laboratory of Pests and Diseases. Research Institute for Tropical Fruit Plants (Balitbu Tropika), Aripan, KM 8, X Koto Singkarak District, Solok Regency, West Sumatra. This research was conducted for 3 months, starting in April 2021 and ending in June 2021. In this study, using a non-factorial, completely randomized design with 5 treatments of cinnamon essential oil with 5 repetitions, each consisting of 4 petridish units, 100 experimental units were obtained. The treatment factors were 0.05%, 0.1%, 0.15%, and 0.20% cinnamon essential oil. The data from this observation were analyzed statistically. If the F count was greater than the F table, then proceed with the DMRT test. Based on the results of the study, it can be concluded that the growth of the fungus Neocitalidium dimidiatum is effective against cinnamon oil, having a significant effect on all observed parameters. The best treatment was cinnamon essential oil with a concentration of 0.20%.